Antimicrobic Activity of IPPU Padang (Ammannia octandra L.f.) Leaves Ethanol Extract against Skin Pathogenic Microbials - Muharni Saputri; Vriezka Mierza; Nirwana Putri (Journal of Fundamental and Applied Pharmaceutical Science, 2022)
Ippu Padang plant (Ammannia octandra L.f.) belongs to the family of Lythraceae, a hardy plant that can grow to a height of 50 cm. According to previous research, Ippu Padang leaves contain glycosides, alkaloids, flavonoids and tannins. The presence of alkaloid compounds, flavonoids and tannins is predicted to have potential as an antifungal agent against fungi and antibacterial agent. This research used an experimental method. The steps included collecting plant material, plant identification, processing plants into Simplicia powder, phytochemical screening of Simplicia powder, extracting Simplicia by maceration method using ethanol solvent, antifungal and antibacterial activity test using agar diffusion method and determination of inhibition diameter of leaf ethanol extract. The results of phytochemical screening showed that ippu Padang leaves contained secondary metabolites, namely alkaloids, flavonoids, glycosides, anthraquinone glycosides, tannins, saponins and steroids. The results also revealed that the concentration with the largest inhibitory diameter was 400 mg/ml, namely 12.4 mm against the Candida albicans, 17.46 mm against the Dermacoccus nishinomiyaensis bacteria, 18.53 mm against the Micrococcus luteus bacteria, 19.38 mm against the Pseudomonas aeruginosa bacteria, and 17.71 mm against Staphylococcus epidermidis bacteria. It was concluded that the ethanol extract of ippu Padang leaves could inhibit the growth of the Candida albicans, the bacteria Dermacoccus nishinomiyaensis, Micrococcus luteus, Pseudomonas aeruginosa and Staphylococcus epidermidis.